Formulating a Competitive Advantage Strategy Using a SWOT Analysis Approach at XYZ Coffee Shop - Abner Aron Ugroseno (Green Publisher, 2025)
The intense competition in the coffee shop industry requires Coffee shop XYZ to possess a strategic advantage. This study aims to formulate a competitive advantage strategy for Coffee shop XYZ using a SWOT analysis approach. The research method applied is descriptive quantitative, with data collection through field observation and literature review. Analysis is conducted by evaluating internal and external factors using the IFAS and EFAS matrices, converting variables into calimatl form to determine the strategic position on the SWOT matrix. Results indicate primary strengths in the grab-and-go concept and strategic locations, despite constraints from dine-in facilities and raw material price fluctuations. Recommended strategies include digital market penetration, service optimization, and product diversification to strengthen brand identity. The study concludes that the company is positioned for aggressive growth by leveraging internal strengths to capture market opportunities.